Paradigm Lost : State Theory Reconsidered - Bratsis, Peter; Aronowitz, Stanley (Book collections on Project MUSE., 2002)
This volume seeks to enrich and complicate current political debates by bringing state theory back to the fore and assessing its relevance to the social phenomena and thought of our day.